Antibacterial Activity of Khaya senegalensis Stem Bark Against Salmonella typhi Isolated from Meat Handling Environments - Saadu Murtala; Shamsudeen Muhammad Muhammad; Samson Blessing Damilola (Journal of Multidisciplinary Science: MIKAILALSYS, 2026)
Against the backdrop of escalating antibiotic resistance, medicinal plants continue to attract attention as potential sources of alternative antibacterial agents. This study evaluated the antibacterial efficacy of crude ethanol stem bark extract of Khaya senegalensis against environmental isolates of Salmonella typhi recovered from slaughter slab surfaces and meat handlers’ aprons. The stem bark extract was subjected to qualitative phytochemical screening, while environmental swab samples were cultured for the isolation and biochemical identification of S. typhi. Antibacterial activity was assessed at concentrations ranging from 12.5 to 100 mg/mL using the agar well diffusion method, whereas the minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) were determined through standard broth dilution and subculturing procedures. Data were analyzed using one-way analysis of variance, with statistical significance set at p < .05. The phytochemical screening revealed the presence of alkaloids, phenolic compounds, tannins, saponins, and steroids. The extract demonstrated concentration-dependent antibacterial activity against all tested isolates, with mean zones of inhibition ranging from 8.00 ± 1.15 mm to 16.00 ± 1.53 mm. The MIC values ranged from 25 to 50 mg/mL, while the MBC was 100 mg/mL for all isolates. Significant differences in antibacterial activity were observed across extract concentrations for most isolates. These findings indicate that K. senegalensis stem bark possesses appreciable antibacterial activity against environmental Salmonella typhi isolates, thereby supporting its traditional medicinal use. The study contributes to the growing evidence that Khaya senegalensis may serve as a promising natural source of antibacterial compounds for addressing antimicrobial resistance and controlling foodborne infections.